Variables in the cuban baseball batter's performance using the Blast Motion baseball sensor - Alfredo Rios Fuentes; Santiago Calero Morales; Ricardo Elaín Eizméndiz Domínguez; Yasser Aguiar Alpízar; Beatriz Sánchez Córdova (Podium, 2020)
The insertion of new technologies in baseball, has optimized the systems for recording and analyzing information both in training and in-game, contributing to a more accurate control of a player's performance. In the present work, the Blast Motion Baseball sensor is applied with the objective of identifying the variables significantly influencing the performance of hitters in Cuban baseball. Batters (N=24) belonging to the National Baseball Series LIX were chosen because it is the Highest-level national event in Cuban baseball. The information was recorded during batting practice, while the batter was performing the task of hitting balls thrown by the coach from the front toss, over the arm at a distance of 30 feet and at a speed of less than 50 mph. The results of Blast Motion Baseball were then compared to the official statistics of the 59th National Baseball Series. The results found show that hitters with higher bat speeds, higher top hand speeds and more power achieve greater performance. Therefore, knowing these characteristics of a hitter's swing in real time helps to perfect the training process and forecasts the hitter´s performance.